PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL, PENEMPATAN KERJA DAN FASILITAS KERJA TERHADAP KEPUASAN KERJA PEGAWAI PADA DINAS SOSIAL KABUPATEN MINAHASA SELATAN - Megawati Rasenyta Rantung; Rita N. Taroreh; Greis M. Sendow (Universitas Sam Ratulangi, 2023)
In an organization or agency, both government and private agencies, human resources have a very important role, namely as a driving force and determining the progress of all activities or work in the organization. This study aims to determine the effect of transformational leadership style, job placement and work facilities on employee job satisfaction at Social Service of Minahasa Selatan Regency. This type of research is quantitative. The population in this study were 147 employees at Social Service of Minahasa Selatan Regency, and the determination of the sample using the Slovin Formula and obtained 60 people as a sample with a precision level set at 10%. The analytical tool in this study uses SPSS version 26 which is used to analyze the independent variable and the dependent variable. The results showed that transformational leadership style, job placement and work facilities simultaneously affect job satisfaction. Transformational leadership style has a positive and insignificant effect on job satisfaction. Job placement has a significant positive effect on job satisfaction. Work facilities have a significant positive effect on job satisfaction. Kata Kunci : gaya kepemimpinan transformasional, penempatan kerja, fasilitas kerja, kepuasan kerja